(untitled) (Journal of Mechanical Engineering, 2015)
For every manufacturing organization, price of the product primarily comprises of manufacturing cost and desired profit. If a company wishes to increase its profit, one way is to reduce the manufacturing cost with maintaining the quality of the product. Waste reduction, especially the (wait) time waste, is an important factor to shrink the manufacturing cost. The purpose of this paper is to identify and address the way to reduce idle time in the apparel manufacturing organization using various line balancing technique to improve productivity and efficiency in domestic context. Line balancing job has been done through the Largest Candidate Rule and Ranked Positional Weight Technique. Using these techniques, a software has been developed to arrange the elemental tasks in the workstation, and to show the balancing efficiencies of each method and other important information. The overall job may be very helpful in some decision making process of the organization. At last an efficient and balanced line has been proposed through the study.